Substituting for rice imports in Ghana - Ragasa, Catherine; Takeshima, Hiroyuki; Chapoto, Antony; Kolavalli, Shashidhara (International Food Policy Research Institute, 2014)
As rice imports surge ahead of production in Ghana, increasing rice production and yields has become a priority. Annual per capita consumption of rice in Ghana grew from 17.5 kg during 1999–2001 to 24 kg during 2010–2011. President Mahama, concerned with rising importation costs, suggested that rice should be produced locally (Asare‐Boadu & Syme 2014). As only 5 percent of global production is traded, local production would also protect consumers from price shocks in the world rice market (World Bank 2013). While substantial investments in national rice production have been made, local production is still not able to keep up with growing demand for rice in Ghana.